Induction of Tissue Factor Expression in Whole Blood: Lack of Evidence for the Presence of Tissue Factor Expression in Granulocytes - Østerud, Bjarne; Rao, L. Vijaya Mohan; Olsen, Jan Ole (Thrombosis and Haemostasis, 2000)
The present investigation was undertaken to explore the effect of platelets, tumor necrosis factor (TNF) and phorbel ester [phorbol 12-myristate 13-acetate (PMA)] on lipopolysaccharide (LPS)-induced tissue factor (TF) activity and TF antigen by using Western blot and ELISA-techniques. LPS was found to induce correlating levels of TF antigen and the activity in monocytes. TNF and PMA, when used alone, failed to induce TF activity and the antigen in monocytes, but enhanced the LPS-induced TF activity and the antigen by 2 to 3-fold. Addition of platelet rich plasma to isolated blood cells enhanced the LPS-induced TF activity but not the antigen levels in monocytes. In contrast to whole platelets, platelet lysates enhanced both LPS-induced TF activity and the antigen. Granulocytes isolated from heparinized plasma incubated for 2 or 24 h with LPS alone or together with PMA, failed to generate TF antigen or the activity. Although granulocyte preparations isolated from whole blood that was incubated for 24 h with LPS and PMA apparently possessed a significant amount of TF activity and the antigen, this could be accounted for by trace levels of contaminating monocytes. Upregulation of LPS-induced TF activity but not the antigen by platelets in the presence of granulocytes suggests that the increased TF activity could be the result of PS enrichment of monocytes by fusion or platelets with activated monocytes.
Keywords: Tissue factor; granulocytes; monocytes; platelets; LPS